Properties of CO$_2$ clathrate hydrates formed in the presence of MgSO$_4$ solutions with implications for icy moons - Safi, E.; Thompson, S.P.; Evans, A.; Day, S.J.; Murray, C.A.; Parker, J.E.; Baker, A.R.; Oliveira, J.M.; Van Loon, J. Th. (Astronomy & Astrophysics, 2017)
There is evidence to suggest that clathrate hydrates have a significant effect on the surface geology of icy bodies in the Solar System. However the aqueous environments believed to be present on these bodies are likely to be saline rather than pure water. Laboratory work to underpin the properties of clathrates in such environments is lacking. We fill this gap by carrying out a laboratory investigation of the physical properties of CO$_2$ clathrates produced in weak aqueous solutions of MgSO$_4$. We use synchrotron X-ray powder diffraction to investigate clathrates formed at high CO$_2$ pressure in ice that has formed from aqueous solutions of MgSO$_4$. We measure the thermal expansion, density and dissociation properties of the clathrates under temperature conditions similar to those on icy Solar System bodies. We find that the sulphate solution inhibits the formation of clathrates by lowering their dissociation temperatures. Hysteresis is found in the thermal expansion coefficients as clathrates are cooled and heated; we attribute this to the presence of the salt in solution. The density derived from X-ray powder diffraction is temperature and pressure dependent. When comparing the density of CO$_2$ clathrates to that of the solution in which they formed, we conclude that they sink in the oceans in which they form. We also find that the polymorph of ice present at low temperatures is Ih rather than Ic, which we attribute to the presence of the MgSO$_4$. We 1) conclude that the clathrate density has implications for their behaviour in satellite oceans as their sinking and floating capabilities are temperature and pressure dependent, 2) conclude that the presence of MgSO$_4$ inhibits the formation of clathrates and in some cases may even affect their structure and 3) report the dominance of Ih throughout the experimental procedure despite Ic being the stable phase at low temperature.
Keywords: QB Astronomy; methods: laboratory: solid state / planets and satellites: surfaces / planets and satellites: individual: Europa / planets and satellites: individual: Enceladus / molecular data